An investigation into EFL learners' motivational dynamics during a group communicative task: A classroom-based case study. (April 2020) - Guo, Yan; Xu, Jinfen; Xu, Xuefen
Abstract: This study examined how a group of Chinese EFL learners' task motivation progressed during a particular group communicative task in a natural classroom context, and what variables were perceived to have affected the students' ongoing motivational dynamics during the task. A mixed-methods approach was adopted to gather a broad range of data, including the participants' ratings of their moment-by-moment task motivation intensity, their corresponding written explanations for the ratings, and focus group interviews. An intact class of 39 s-year college students participated in the study. The results revealed not only fluctuations in motivation on a minute-by-minute basis during task performance, but also variations in motivational change patterns across learners, suggesting that task motivation is dynamic even in the very short term. Attributions of such fluctuations, as perceived by the participants, included a multitude of immediate situational factors associated with behavioral, cognitive, motivational, linguistic, and contextual influences. In particular, the act of actively presenting views enhanced their motivation to the greatest degree, while a shortage of conceptual preparation (i.e. having no ideas to share) inhibited it to the largest extent. Pedagogical implications are provided based on these findings.